Parametric analysis of composite tubular adhesive joints bonded by the bi-adhesive technique - André Lima Faria; Raul Duarte Salgueiral Gomes Campilho (Academia Materials Science)
Adhesive bonding plays a fundamental role in various industries, including aerospace, aeronautics, and automotive sectors. Unlike traditional mechanical joints, adhesive joints offer an efficient approach with fewer components, leading to weight reduction in the final structure. Additionally, these joints facilitate the joining of dissimilar materials, while distributing applied loads more uniformly, resulting in better stress distributions compared to conventional joining techniques. Within this context, the integration of adhesive bonds in joggle tubular structures presents a viable alternative to join tubes with identical diameter. The bi-adhesive technique involves using a brittle adhesive in the inner overlap region, and a ductile adhesive at the overlap edges, aiming to improve load transfer. The objective of this study is to conduct a numerical analysis using cohesive zone modeling (CZM) to investigate the tensile behavior of joggle tubular adhesive joints between composite adherends bonded by the bi-adhesive technique. Initially, the proposed CZM approach is validated against experimental data. Subsequently, the study focuses on numerically assessing the tensile strength of the joints and testing different bi-adhesive joint options, aiming to improve the maximum load (Pm), displacement at Pm (δat Pm), and energy absorbed at failure (Ef). Validation of the cohesive models has been successfully achieved. In conclusion, it was found that depending on the bi-adhesive conditions, improvements are possible to obtain over single-adhesive joints.